Variação diária e anual de freqüência e atividade do Boto Cinza Sotalia guianensis em Pipa, Nordeste do Brasil - Silveira, Fernando Roberto Guilherme (2006)
The aim of this study was to investigate the daily and annual variation in frequency and in activity of an estuarine dolphin population, Sotalia guianensis, in Brazilian northeastern. Thus we estimated the daily variation and seasonality in frequency of adult and immature and in behavior of socialization, aerial activity, foraging of a boto equatorial population in the Curral inlet (6º13 00 S; 35º3 36 W). We detect some variation. Thus we associate the daily variation with daily period, tide fluctuation and annual season. And the seasonality variation we associate with the fotoperíodo and precipitation variation. From October 1999 to September 2003, through collect four times at month, we made instantaneous record at each five minute in six hours of survey. The surveys hours were ranged into light time of 24 hours, that is, between 06:00 and 17:00 o clock. These observations were developed simultaneous for two observers in a land-based survey at coastline cliff top of which observer have a fully visualization of whole inlet. We found that animals were more active and frequent during the morning. They were more active during low tide than high tide. However they did not show association with tide. We found yet that in a period from June to November (winter-spring) there was the highest socialization, aerial activity and foraging frequency. However adult and immature individual number did not have significance variation along the year. The larger concentration of this behaviors were not associate with photoperiod neither precipitation in the region. These results showed the existence of behavioral daily variation and seasonality in a species that live in equatorial region